Proses Pemberdayaan Petani Porang Oleh Aktor-Aktor Lokal Di Desa Kepel Kabupaten Madiun - Prasetyo, Yulinda; Anugrahini, Triyanti (Universitas Medan Area, 2024)
This research describes the efforts of local actors in the process of empowering porang cultivation in Giringan Hamlet, Kepel Village, and Madiun Regency. Through a qualitative research approach, this research aims to examine how local actors in Kepel Village can become initiators of empowering porang cultivation through the innovations created. The results showed that empowerment was initiated by several farmers who tried to overcome the condition of being powerless by diversifying agriculture. Not stopping at individual achievements, porang farmer group were formed as a forum for carrying our empowerment activities, starting with providing initial information about porang, selecting quality seeds, appropriate planting methods, and harvest marketing strategies. The members of the porang farmer group have grown, starting with 11 members in 2016 to 106 members in 2023. Previously, porang was only considered a wild plant, currently, 98% of farmers in Giringan Hamlet have adopted porang as their agricultural diversification. The efforts of local actors to empower farmers have led to multidimensional empowerment, where the empowerment process starts from individual development and then develops towards broader social change.